CUSTOMER RELATIONS MANAGEMENT IMPLEMENTATION ANALYSIS THROUGH CUSTOMER ENGAGEMENT PROGRAM PT. GRAB INDONESIA IN YOGYAKARTA (Descriptive Study of Grab Temu Seru, Ayoyog and Jogja Istimewa in Achieving Consumer Loyalty Grab Indonesia in Yogyakarta) - Intan Haniyah Herdiana; Dewi Novianti; Ida Wiendijarti (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
The problems that occur in PT Grab Indonesia that directly impact on its customers, making the company should seek to establish good relations with external parties. The purpose of this research is to know the implementation of customer relationship management through customer engagement program PT Grab Indonesia in Yogyakarta and know the supporting and inhibiting factors of program implementation. The results in this study indicate that the programs aimed at customer PT Grab Indonesia Yogyakarta include Grab Temu Seru program, promotion program